A 420 nm Blue Diode Laser for the Potential Rubidium Optical Frequency Standard *Supported by the China Academy of Space Technology Foundation under Grant No CAST-2015-5-10, the National Hi-Tech Research and Development Program, and the National Natural Science Foundation of China under Grant No 91436210. (July 2017) - Zhang 张, Sheng-Nan 盛楠; Zhang 张, Xiao-Gang 晓刚; Tu 涂, Jian-Hui 建辉; Jiang 蒋, Zhao-Jie 招杰; Shang 商, Hao-Sen 浩森; Zhu 祝, Chuan-Wen 传文; Yang 杨, Wei 炜; Cui 崔, Jing-Zhong 敬忠; Chen 陈, Jing-Biao 景标
Abstract : We report a 420 nm external cavity diode laser with an interference filter (IF) of 0.5 nm narrow-bandwidth and 79% high transmission, which is first used for Rb optical frequency standard. The IF and the cat-eye reflector are used for selecting wavelength and light feedback, respectively. The measured laser linewidth is 24 kHz when the diode laser is free running. Using this narrow-linewidth IF blue diode laser, we realize a compact Rb optical frequency standard without a complicated PDH system. The preliminary stability of the Rb optical frequency standard is 2 × 10 − 13 at 1 s and decreases to 1.9 × 10 − 14 at 1000 s. The narrow-linewidth characteristic makes the IF blue diode laser a well suited candidate for the compact Rb optical frequency standard.